Kinetic affinity index informs the divisions of nitrate flux in aerobic denitrification - Ruan, Yunjie (2022)
Aerobic denitrification is attracting increasing attention since its advantage of complete nitrogen removal in a single aerobic reactor with simplified configurations. This study investigated the nitrate kinetic affinity (half-saturation index, Km) by an isolated aerobic denitrifier named P. balearica strain RAD-17. It turned out that strain RAD-17 had a high Km of 162.5 mg-N/L and maximum nitrate reduction rate of 21.7 mg-N/(L•h), enabling it to treat high-strength nitrogen wastewater with high efficiency. Further analysis illustrated that Km was the critical value for the change of growth yield rate along initial nitrate concentrations. Nitrogen balance results elucidated an opposite nitrogen flux to cell synthesis and nitrogen loss during aerobic denitrification. Moreover, the expression of functional genes provided proofs for these phenotypic results at transcriptional level. Consequently, Km could be an indicator for nitrate flux division directing to respiration and assimilation in aerobic denitrifiers, shedding light on its regulation for wastewater treatment.